Kinetic study of the thermal dehydration of borogypsum - Elbeyli, IY; Piskin, S (ELSEVIER SCIENCE BV, 2004)
In Turkey, a large amount of borogypsum waste is discharged by the economically important boric acid industry. Calcination of this waste provides a promising technique not only for recovering an economic value but also for reducing its environmental impact. The aim of this work is to study the thermal behavior of borogypsum, which contains gypsum crystals, boron oxide and some impurities under nonisothermal conditions in air atmosphere by using thermogravimetry and differential thermal analysis techniques (TG-DTA). Experiments were carried out at temperatures ranging from ambient to 773 K at different heating rates. The temperatures of conversion from gypsum to hemihydrate and anhydrite states were determined. Various methods were used to analyze the TG and DTA data for determination of reaction kinetics. The activation energy and frequency factor were calculated for dehydration of borogypsum. Activation energy values of the main dehydration reaction of borogypsum were calculated to be approximately 95-114 kJ mol(-1). (C) 2004 Elsevier B.V. All rights reserved.
Keywords: borogypsurn; kinetics; dehydration; thermal behavior; PORTLAND-CEMENT; THERMOGRAVIMETRIC DATA; BORON; BEHAVIOR; WASTE; Engineering; Environmental Sciences & Ecology